Optimization of PAPR Reduction Technique for OFDM Signal Based Discrete Multiwavelet Critical-Sampling Transformin MC- CDMA using Selected Mapping with Phase Modification Method - Mohammed Aboud Kadhim (Journal of Madenat Alelem University College, 2017)
Multi-carrier code-division multiple access (MC-CDMA) is anextensively known transmission technique for high speed data communication. In MC-CDMA, transmission is performed in parallel on various frequencies. This technique is widely sought after for the transmission of digital data via the media offadding channels. This paper showcases original contribution to the field of “peak-to-average power ratio (PAPR)” reductioneffect by using “Multiwavelet Critical-Sampling Transform (DMWCST)” in the developmental “MC-CDMA systems”. In this study, primarily oriented towards the selected mapping techniques and phase modification was used. As well showcase how selected mapping with phase modification can be applied to mitigate PAPR since they are signal distortionless and their complexity is lesser compared to other techniques.